The Effect of e-Purchasing Implementation Through E-Catalogue on Procurement Performance - Suryani, Eny; Nugroho, Kandung Sapto; Cadith, Juliannes (PT Aksara Indo Rajawali, 2025)
Procurement of goods and services (PBJ) is a fundamental aspect of government agency operations. With the development of information technology, the implementation of e-purchasing through e-catalogues has become an integral part of the procurement system in the public sector. This study aims to analyze the effect of e-purchasing implementation through e-catalogues on procurement performance at the Indonesian Food and Drug Monitoring Agency (Badan POM). Using a quantitative method and an associative causal approach, this study collected data from 156 respondents directly involved in the procurement process. The analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study indicate that the implementation of e-purchasing through e-catalogues has a positive and significant impact on procurement performance, with a strong contribution to improving the efficiency, effectiveness, transparency, and accountability of the procurement process. These findings support the application of digital technology in public procurement and provide implications for policies and strategies to improve procurement performance in the government sector.